2016
DOI: 10.1186/s40643-016-0119-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of glycolipid biosurfactant produced by a Pseudomonas otitidis strain isolated from Chirimiri coal mines, India

Abstract: Background: Biosurfactants (BSs) are amphipathic, surface active molecules produced by microorganisms and can reduce the surface tension and interfacial tension. The present study emphasizes the isolation and structural characterization of the BS produced by Pseudomonas otitidis P4.Results: An efficient BS producing bacterial strain isolated from the unexplored coal mining site of Chirimiri, India was identified as P. otitidis P4 based on morphological, biochemical and 16S rRNA gene sequence analysis. The surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 71 publications
(93 reference statements)
3
19
0
Order By: Relevance
“…The Fourier transform infrared spectroscopy (FTIR) analysis of the biosurfactant produced from BSP9 clearly reveals the presence of functional groups that typically belong to glycolipids. The spectrum ( Figure 1 ) was consistent with the structure of glycolipids already reported in the literature [ 58 , 59 , 60 ]. The IR spectrum shows absorption bands ranging between 3650–3134 cm −1 , which indicate the presence of free -OH group arising as a result of H bonding of polysaccharides and/or –OH stretching of carboxylic acid.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The Fourier transform infrared spectroscopy (FTIR) analysis of the biosurfactant produced from BSP9 clearly reveals the presence of functional groups that typically belong to glycolipids. The spectrum ( Figure 1 ) was consistent with the structure of glycolipids already reported in the literature [ 58 , 59 , 60 ]. The IR spectrum shows absorption bands ranging between 3650–3134 cm −1 , which indicate the presence of free -OH group arising as a result of H bonding of polysaccharides and/or –OH stretching of carboxylic acid.…”
Section: Resultssupporting
confidence: 89%
“…Two bands at wavenumber 1748 cm −1 and 1712 cm −1 denote –C=O stretching arising from the ester groups of lipids and fatty acids (-C=O in COOH), and bands at wavenumber 1396 cm −1 signify C-H and OH deformation vibrations of carbohydrates that may be arising due to the presence of rhamnose units in the biosurfactants [ 61 ]. A small peak at wavenumber 2358 cm −1 is likely due to the presence of phosphines (P-H 3 ) in the biosurfactant [ 59 ]. The range of spectra below 1000 cm −1 represents C-H, C-O and CH 3 vibrations [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Emulsion layers formed by B14 BS obtained when cells are grown on an optimum culture medium, were stable under a wide range of pH (2–10), and temperature (30–37°C). This result was in agreement with the glycolipid derived from Pseudomonas otitidis , isolated from a coal mine, whose E24 could still be detected when exposed to pH 3–11, and the temperature was as high as 80–100°C ( Singh and Tiwary 2016 ). The stability studies on glycolipid BS derived from P. aeruginosa HAK01 indicated that this BS was able to function under a wide range of temperatures (40–121°C) and pH (4–10) ( Khademolhosseini et al 2019 ).…”
Section: Discussionsupporting
confidence: 87%
“…In order to investigate our glycolipid potential application, antimicrobial activity of cell-free broth containing B14 BS derived from cultures grown on an optimized medium was tested. Although biosurfactant will typically be used in actual application in the form of pure compounds, the cell-free supernatant could be used as a pre-screening process for stability studies and antimicrobial tests ( Singh and Tiwary 2016 ; Mouafo et al 2018 ). At this stage, we then selected to use the cell-free supernatant from strain B14 for these studies, as it is also less time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…TMB1 has utilized NaNO 3 as the best nitrogen source for maximum growth and production of biosurfactant at optimum temperature (30 °C) and pH (7.2). Singh and Tiwary reported yeast extract as the best nitrogen source for the yield of biosurfactants by Pseudomonas otitidis P4 strain . But for Achromobacter sp.…”
Section: Discussionmentioning
confidence: 99%